Highly differentiated population structure of a Mangrove species, Bruguiera gymnorhiza (Rhizophoraceae) revealed by one nuclear GapCp and one chloroplast intergenic spacer trnF–trnL - Sumiko, Minobe; Shingo, Fukui; Rumiko, Saiki; Tadashi, Kajita; Suchitra, Changtragoon; Ab Shukor, Nor Aini; Mohamad, Abdul Latiff; Ramesh, B. R.; Osamu, Koizumi; Tsuneyuki, Yamazaki (Springerlink, 2010)
To evaluate the genetic diversity of a mangrove species and clarify the genetic structure of its populations, we studied nucleotide polymorphism in two DNA regions of Bruguiera gymnorhiza collected from the southern islands of Japan, Thailand, Malaysia, Indonesia, Micronesia, and India. The two DNA sequences were the chloroplast (cp) intergenic spacer between trnL and trnF genes (ca. 300 bp), and a part (ca. 550 bp) of the nuclear gene coding for glyceraldehyde-3-phosphate dehydrogenase (GapCp). Little polymorphism was found within each of the three geographical regions, Pacific Ocean, Bay of Bengal and Arabian Sea. Throughout the vast regions east